The Doctoral Journey of a Yemeni Student in Indonesia: A Narrative Inquiry into the Experiences of Pursuing English Language Education - Mustagis, R Muhammad Satria Gyas (JOLLT Journal of Languages and Language Teaching, 2025)
The internationalization of higher education has generated unique opportunities for cross-cultural doctoral experiences; however, notable gaps exist in understanding the experiences of Middle Eastern students within Southeast Asian academic environments. Yemeni students pursuing advanced degrees in Indonesia, particularly in English Language Teaching programs, have been largely overlooked in international education research despite the increasing trends in educational migration. This research examines the experiences of Yemeni doctoral student enrolled in English Language Teaching programs in Indonesia, employing a narrative inquiry methodology. A qualitative narrative inquiry method was employed, using semi-structured interviews conducted with a 33-year-old Yemeni doctoral student enrolled at Universitas Negeri Malang. The analysis of data utilized the Labov framework, focusing on the components of abstract, background, key events, outcome, reflection, and closing statement. Findings indicated strategic patterns of academic mobility, wherein students utilized prior educational experiences to facilitate systematic academic advancement. Cultural identity has emerged as a catalyst for academic excellence, challenging deficit-oriented perspectives in the literature on international education. Students encountered various challenges across linguistic, temporal, and cultural domains, necessitating ongoing adaptation strategies. The study concludes that Indonesia is an effective destination for Middle Eastern doctoral candidates when comprehensive institutional support systems are in place. These findings mandate immediate policy interventions requiring universities to implement culturally responsive supervision frameworks, establish specialized support infrastructures, and develop assessment protocols measuring institutional effectiveness in fostering international doctoral success across diverse demographic populations.